The pear ‘Packham’s Triumph’ - Faoro, Ivan Dagoberto (2018)
The pear cv. Packham’s Triumph is described in this article as its origin, climate adaptation, botanical and agronomic characteristics. It is also presented the main morphological, physiological aspects, plant disease resistance, rootstocks, demands for pollinating plants and storage.